Analisis Pendapatan Usahatani Jagung Pipil Di Desa Tombolikat Kecamatan Tutuyan Kabupaten Bolaang Mongondow Timur - Apande, Regina; Kumaat, Ribka Magdalena; Laoh, Olly Esry Harryani (AGRI-SOSIOEKONOMI, 2023)
So this study aims to calculate the Income of Pipil Corn Farming in Buttonikat Village, Tutuyan District, East Bolaang Mongondow Regency. This research was conducted during December 2021 and January 2022. The data used in this research are primary data and secondary data. Primary data was obtained through direct interviews with 10 respondents using a questionnaire. And secondary data obtained through books, journals, and literature related to this research topic. The results of this study indicate that the average income received by corn farmers in the village of Tombolikat, District of Tutuyan, East Bolaang Mongondow Regency with Corn Farming, is Rp. 4,999,997. and the income per hectare is Rp. 3,571,426.